In-situ monitoring of the unstable bacterial adhesion process during wastewater biofilm formation: A comprehensive study. (July 2020) - Wang, Jinfeng; Liu, Qiuju; Dong, Deyuan; Hu, Haidong; Wu, Bing; Ren, Hongqiang
Graphical abstract: Highlights: Biofilm unstable adhesion phase was quantitatively characterized via RTCA on-line. High concentrations of bacteria shorten the reversible adhesion process. Shear stress increases the reversibility of bacterial adhesion. Bacterial motility regulates the unstable adhesion process. Proteins in EPS may substantially impact the initial adhesion process. Abstract: The initial bacterial adhesion phase is a pivotal and unstable step in the formation of biofilms. The initiation of biofilm formation is an unstable process caused by the reversible adhesion of bacteria, which is always time-consuming and yet to be elucidated. In this study, impedance-based real time cell analysis (RTCA) was employed to comprehensively investigate the initial bacterial adhesion process. Results showed that the time required for the unstable adhesion process was significantly ( p  < 0.05) reduced by increasing the initial concentration of bacteria, which is mainly attributed to the large deposition rate of bacteria at high concentrations. In addition, the unstable adhesion process is also regulated by shear stress, derived in this work from orbital shaking. Shear stress improves the reversibility of unstable bacterial attachment. Furthermore, attachment characteristics during the unstable phase vary between different species of bacteria ( Sphingomonas rubra, Nakamurella multipartita and mixed bacteria). The S. rubra strain and mixed culture were more prone to adhere to the substratum surface during the unstable process, which was attributed to the smaller xDLVO energy barrier and motility of species in comparison with N. multipartita . Meanwhile, the molecular composition of extracellular polymeric substances (EPS) in the initial attachment phase presented a significant difference in expressed proteins, indicating the important role of proteins in EPS that strengthen bacterial adhesion. Overall, these findings suggest that during the biofilm reactor start-up process, seed sludge conditions, including the bacterial concentration, composition and hydraulics, need to be carefully considered.